Disinfection of Stethoscope and Non-Infrared Thermometer: Practices of Physicians in Ethiopia in the Era of COVID-19 - Sahiledengle B; Tekalegn Y; Bekele K; Tesemma A; Edward Quisido BJ (Dove Medical Press, 2021)
Biniyam Sahiledengle,1 Yohannes Tekalegn,1 Kebebe Bekele,2 Abdi Tesemma,2 Bruce John Edward Quisido3 1Madda Walabu University Goba Referral Hospital, School of Health Sciences, Public Health Department, Goba, Bale, Ethiopia; 2Madda Walabu University Goba Referral Hospital, Department of Surgery, Goba, Bale, Ethiopia; 3Madda Walabu University Goba Referral Hospital, Department of Nursing, Goba, Bale, EthiopiaCorrespondence: Biniyam SahiledengleMadda Walabu University Goba Referral Hospital, School of Health Sciences, Public Health Department, P.o. Box: 76, Goba, Bale, EthiopiaTel +251 911 56 0309Email biniyam.sahiledengle@gmail.comBackground: Stethoscopes and non-infrared thermometers are the customary medical equipment used by the physicians on a daily basis, among various patients. With the rise of potential infections in the healthcare facilities and the transmission nature of the current COVID-19 pandemic, consistent and correct disinfections of these devices after each use should not be pardoned. This study, therefore, aimed to assess the level of stethoscope and non-infrared thermometer disinfection practices among physicians involved in direct patient contact during the COVID-19 pandemic.Methods: A web-based cross-sectional survey was conducted among physicians working in Ethiopia to assess their practice of stethoscope and non-infrared thermometer disinfection. The online survey was circulated using an anonymous and self-reporting questionnaire via Google form with a consent form appended to it. The developed Google form link was shared with physicians through their email addresses and social media pages. A descriptive summary was computed and presented by tables and figures. Multivariable logistic regression model was used to identify factors associated stethoscope and non-infrared thermometer after every use.Results: The proportion of stethoscope and non-infrared thermometer disinfections after every use was 13.9% (95% CI: 10.9– 17.6) and 20.4% (95% CI: 16.7– 24.5), respectively. Taking COVID-19 training (AOR: 2.52; 95% CI: 1.29– 4.92) and the availability of stethoscope disinfection materials at the workplace (AOR: 3.03; 95% CI: 1.29– 7.10) were significantly increased the odds of stethoscope disinfection after every use. The odds of stethoscope disinfection after every use was significantly decreased for those who reported the use of shared stethoscope (AOR: 0.34; 95% CI: 0.12– 0.92).Conclusion: Only a wee share of the respondents reported that they have disinfected their stethoscopes and non-infrared thermometers after every use – possibly jeopardizing both patients and clinicians safety, particularly during the COVID-19 pandemic.Keywords: COVID-19, stethoscope, non-infrared thermometer, physicians, disinfection